2021
DOI: 10.3389/fmicb.2021.723498
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Cell Wall Biosynthesis Modulates Bone Invasion and Osteomyelitis Pathogenesis

Abstract: Staphylococcus aureus invasion of the osteocyte lacuno-canalicular network (OLCN) is a novel mechanism of bacterial persistence and immune evasion in chronic osteomyelitis. Previous work highlighted S. aureus cell wall transpeptidase, penicillin binding protein 4 (PBP4), and surface adhesin, S. aureus surface protein C (SasC), as critical factors for bacterial deformation and propagation through nanopores in vitro, representative of the confined canaliculi in vivo. Given these findings, we hypothesized that ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 67 publications
1
27
0
Order By: Relevance
“…The interaction of the FSL NPs with the Gram-positive bacterium and the changes in the cell morphology and structure of the cells were further assessed using SEM ( Figure 3 B). S. aureus appear as smooth spheres with size ranging from 500 nm to 1 µm in diameter [ 30 ]. The exposure of the bacteria to empty NPs did not alter the bacterial cell morphology and the cell wall structure remained intact, similar to the control (non-treated bacteria).…”
Section: Resultsmentioning
confidence: 99%
“…The interaction of the FSL NPs with the Gram-positive bacterium and the changes in the cell morphology and structure of the cells were further assessed using SEM ( Figure 3 B). S. aureus appear as smooth spheres with size ranging from 500 nm to 1 µm in diameter [ 30 ]. The exposure of the bacteria to empty NPs did not alter the bacterial cell morphology and the cell wall structure remained intact, similar to the control (non-treated bacteria).…”
Section: Resultsmentioning
confidence: 99%
“…This finding suggests that implant microarchitecture is incredibly important and may offer bacteria a submicron reservoir to evade clearance by the immune system. The work of Masters et al ( 66 ) expanded upon these findings by investigating the role of S. aureus cell wall synthesis machinery and surface adhesins in OLCN invasion. The authors established a model of bacterial osteomyelitis by placing stainless steel pins inoculated with various mutant strains of S. aureus into the medial tibia of mice.…”
Section: Small Animal Modelsmentioning
confidence: 99%
“…Numerous antimicrobials cannot penetrate and reach adequate concentrations for bactericidal efficacy in bone compared to soft tissue (Thompson and Townsend, 2011;Tuchscherr et al, 2016;Alder et al, 2020). Furthermore, some bacteria internalize and survive within bone cells for a long period of time, which contributes to insufficient treatments (Tuchscherr et al, 2016;De Mesy Bentley et al, 2018;Yang et al, 2018;Muthukrishnan et al, 2019;Masters et al, 2021). Access to the intracellular environment protects this pathogen from the action of the host immune response and antimicrobials, promoting persistence (Tuchscherr et al, 2011;Horn et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although different studies have described that S. aureus can survive for long periods within osteoblasts (Kalinka et al, 2014;Ji et al, 2020;Bongiorno et al, 2021;Gunn et al, 2021;Marro et al, 2021), the mechanisms that may explain the persistence within bone cells are still unknown. In addition to osteoblasts, several studies have revealed osteocytes as possible niche for bacteria within bone tissue (De Mesy Bentley et al, 2018;Yang et al, 2018;Krauss et al, 2019;Masters et al, 2021). Recently, the persistence of S. aureus in bone tissue was associated with its capacity to invade the osteocyte lacunocanalicular network (OLCN; Masters et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation